Management of Ano-Rectal Malformations in a Tertiary Level Children’s Hospital of Nepal - Thapa, Bijay; Basnet, Balmukunda; Pun, Madhusudan; Thapa, Anupama (Journal of Nepal Paediatric Society, 2013)
Introduction: Ano-rectal malformation (ARM) comprises a wide spectrum of diseases that involves the distal anus and rectum as well as the urinary and genital tracts. The factors that need to be considered during treatment are the type of anomaly, associated anomalies and patients general condition. The aim of this study is to analyze the types of anorectal malformations and their management in a tertiary level children’s hospital. Materials and Methods: The medical records of patients with the diagnosis of anorectal malformation managed in the hospital during a period of January 2009 to January 2014 were reviewed. Results: There were 187 cases of ARM 126 (67.37%) males and 61 (32.62%) females. High/Intermediate type was 129 (68.98%). Low ARM was 58 (31.01%). In male high type ARM with recto-urethral fistula was seen in 60 (47.61%). ARM with Rectovestibular fistula(RVF) was seen in 40 (65.5%) female. High and intermediate ARMs were managed initially with colostomy and low ARM with primary anoplasty. ARM with rectovestibular fistula in females were managed with Anterior Sagittal Anorectoplasty without colostomy. Common cloaca in female was managed initially with colostomy followed by posterior sagittal ano-recto-vagino-urethroplasty. Colostomy closure was done after adequate size of anus was achieved with anal dilation. Conclusion: The type of ARM in newborn is diagnosed by perineal examination and X-rays. Low type ARM was managed by primary surgery without colostomy. High anomaly and complex defect was treated with stage surgeries. DOI: http://dx.doi.org/10.3126/jnps.v33i3.8190 J. Nepal Paediatr. Soc. 2013;33(3):196-200